Donor and recipient genetic variants in drug metabolizing enzymes and transporters affect early tacrolimus pharmacokinetics after liver transplantation - Alexandra D. Ladd; Isabella Angeli-Pahim; Duncan Lewis; Curtis Warren; Satyavardhan Nittu; Jatinder Lamba; Sergio Duarte; Ali Zarrinpar (Scientific Reports)
Abstract This study examines the influence of single nucleotide polymorphisms in drug metabolizing enzymes CYP3A4, CYP3A5, and UGT1A4, and the transporter ABCB1 on tacrolimus dose requirements and blood trough level variability in the period immediately after liver transplantation. We analyzed genotypes for these genes in 61 adult liver transplant recipients who received tacrolimus and their respective donors. Significant findings include increased average daily deviation (ADD) from the therapeutic range in patients with: donor CYP3A4*22 GG (1.68 [1.01, 2.29] versus 0.68 [0.42, 1.46] ng/mL/day, p = 0.016), recipient ABCB1 rs2032582 CT/TT (2.07 [1.68, 2.39] versus 1.37 [0.76, 1.95] ng/mL/day , p = 0.013), and donor UGT1A4*3 TT (1.69 [1.02, 2.42] versus 1.33 [0.54, 1.79] ng/mL/day , p = 0.043). Additionally, higher tacrolimus concentration/weight-adjusted dose ratios [C0/D ratio, (ng/mL)/(mg/kg/d)] were observed in recipients with CYP3A4*1B rs2740574 genotype TT (77.5 [60.7, 143.8] versus 47.5 [26.3, 64.0] (ng/mL)/(mg/kg/d), p = 0.0001), or CYP3A5*3 rs776746 genotype GG (74.9 [55.7, 147.4] versus 59.3 [36.1, 79.0] (ng/mL)/(mg/kg/d), p = 0.011), and in donor livers with CYP3A4*22 genotype GA/AA (131.5 [86.2, 187.1] versus 68.2 [47.1, 108.7] (ng/mL)/(mg/kg/d), p = 0.028). These findings demonstrate that genetic polymorphisms in both donor and recipient significantly affect tacrolimus dose requirements and the ability to maintain the target therapeutic tacrolimus levels in the immediate post-transplant period, emphasizing the role of precision medicine in optimizing immunosuppression therapeutic drug dosing.